Long‐term control of olfactory neuroblastoma in a dog treated with surgery and radiation therapy. Issue 7 (July 2017) - Gumpel, E; Moore, AS; Simpson, DJ; Hoffmann, KL; Taylor, DP
Abstract : Background: Olfactory neuroblastoma is a rare malignancy of the nasal cavity in dogs that is thought to arise from specialised sensory neuroendocrine olfactory cells derived from the neural crest. Case report: An 8‐year‐old dog was presented for reclusiveness and pacing. On CT and MRI, a contract‐enhancing mass was disclosed within the rostral fossa, extending caudally from the cribriform plate into the left nasal sinus. Surgical excision was performed and the diagnosis was histological grade III (Hyams grading scheme) olfactory neuroblastoma. Based on human CT criteria this was high stage (modified Kadish stage C). Surgical excision was incomplete and was followed by curative‐intent radiation therapy using a linear accelerator to a total dose of 48 Gy. Conclusion: The dog survived 20 months after diagnosis. Although olfactory neuroblastoma is a rare tumour in dogs, aggressive local therapy may allow for prolonged survival, even when the tumour is advanced.